The reluctant revolutionary : Dietrich Bonhoeffer's collision with Prusso-German history - Moses, John A. (John Anthony), 1930- (Berghahn Books, 2009)
Dietrich Bonhoeffer was a uniquely reluctant and distinctly German Lutheran revolutionary. In this volume, the author, an Anglican priest and historian, argues that Bonhoeffer's powerful critique of Germany's moral derailment needs to be understood as the expression of a devout Lutheran Protestant. Bonhoeffer gradually recognized the ways in which the intellectual and religious traditions of his own classthe Bildungsbrgertumwere enabling Nazi evil. In response, he offered a religiously inspired call to political opposition and Christian witnesswhich cost him his life. The author investigat.